2011
DOI: 10.1371/journal.pone.0026281
|View full text |Cite
|
Sign up to set email alerts
|

Excess Risk of Maternal Death from Sickle Cell Disease in Jamaica: 1998–2007

Abstract: BackgroundDecreases in direct maternal deaths in Jamaica have been negated by growing indirect deaths. With sickle cell disease (SCD) a consistent underlying cause, we describe the epidemiology of maternal deaths in this population.MethodsDemographic, service delivery and cause specific mortality rates were compared among women with (n = 42) and without SCD (n = 376), and between SCD women who died in 1998–2002 and 2003–7.ResultsWomen with SCD had fewer viable pregnancies (p: 0.02) despite greater access to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 27 publications
5
43
1
2
Order By: Relevance
“…The current study has showed that the incidence of adverse pregnancy outcomes was high among SCD deliveries with more than two thirds of all SCD deliveries ending in one or more adverse outcomes. This high incidence of adverse outcomes concurs with the findings by other international studies that generally report increased adverse pregnancy outcomes among SCD deliveries [5][6][7][8][9][10][11]13,[17][18][19]]. …”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The current study has showed that the incidence of adverse pregnancy outcomes was high among SCD deliveries with more than two thirds of all SCD deliveries ending in one or more adverse outcomes. This high incidence of adverse outcomes concurs with the findings by other international studies that generally report increased adverse pregnancy outcomes among SCD deliveries [5][6][7][8][9][10][11]13,[17][18][19]]. …”
Section: Discussionsupporting
confidence: 90%
“…An increased risk of pre-eclampsia and pregnancy-induced hypertension have been reported in some studies [6,14] but denied by others [5,10,11,15]. Likewise increased risk for hemorrhage in SCD pregnancy and maternal mortality have been reported by some studies [5,7,[16][17][18] but not all [6,10-11, 13,15]. The above findings conclude that adverse perinatal and maternal outcomes are significant in SCD.…”
Section: Open Accessmentioning
confidence: 77%
See 3 more Smart Citations